Restoring stability - 4 in 1 quadriceps plasty for habitual patella dislocation in a ten-year-old child: a case report - Rao, Sushanth S.; Balemane, Sharat; Puthenpurakal, Verghese M. (International Journal of Research in Orthopaedics, 2024)
Complex clinical and surgical challenges accompany both congenital or fixed dislocations and obligatory or habitual patellar dislocations. Habitual dislocation of the patella is the most severe type of patellar instability and frequently call for surgical intervention. Various surgical procedures have been documented to address habitual patellar dislocation. Since no approach is 100% effective, a combined approach of techniques is recommended for the surgical treatment of habitual patellar dislocation. This article aims to describe the 4-in-1 quadriceps plasty procedure used to stabilize a 10-year-old child’s fixed and habitual patellar dislocation.